DEPRESSION, ANXIETY, AND STRESS AMONG STUDENTS IN SURABAYA DURING COVID-19 PANDEMIC - Patrika, Fauziah; B.Villaruel, Rossandrew (Insight: Jurnal Ilmiah Psikologi, 2021)
This study aims to determine the prevalence and levels of depression, anxiety, and stress among students during the COVID-19 pandemic in Surabaya. This research also investigates the relationship among levels of stress, anxiety, and depression. This study used a cross sectional approach as the research design and purposive sampling as the sampling technique. Participants in this study were 207 active students of the Faculty of Psychology, Hang Tuah University, Surabaya. The instrument used in this research is the DASS-42 questionnaire distributed online. Data analysis was conducted using Pearson correlation test. The results of data analysis showed that there was a strong positive relationship between depression level and anxiety level (p = 0.000, p < 0.05), strong positive relationship between depression level and stress level (p = 0.000, p < 0.05), as well as strong positive relationship between stress levels and anxiety levels (p = 0.000, p < 0.05). In addition, this research results explained that students have mild to very severe anxiety (36.3%), stress (31.9%), and depression (31.8%) during the Covid-19 pandemic. The results of this study are expected to provide information and support in overcoming the psychological problems of students during the Covid 19 pandemic.